2010
DOI: 10.1007/s10530-010-9743-6
|View full text |Cite
|
Sign up to set email alerts
|

Insect assemblages change along a gradient of invasion by a nonnative grass

Abstract: Because invasions by nonnative plants alter the structure and composition of native plant communities, invasions can alter the function of ecosystems for animals that depend on plants for food and habitat. We quantified effects of an invasion by a nonnative grass on the insect community in grasslands of southeastern Arizona. We sampled insects on 54 1-ha plots established across a gradient of invasion by Lehmann lovegrass (Eragrostis lehmanniana Nees), a perennial species native to southern Africa. Between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 48 publications
2
31
2
Order By: Relevance
“…According to this second hypothesis, we also would expect a unimodal variation in herbivore richness along the gradient of invasion by nonnative grasses through the effect of past disturbances on host plants. Why did we find a peak in insect richness at intermediate invasion levels, whereas several previous studies have reported a monotonic decline in insect richness in habitats invaded by nonindigenous plants (e.g., Litt and Steidl 2010;Yoshioka et al 2010)? A simple explanation is that endophagous herbivores are less susceptible to changes in vegetation structure (see Pearson 2009) and to harsher abiotic conditions (e.g., higher temperature and/or lower humidity promoting desiccation) compared to ectophagous herbivores, predators and other non-herbivorous insects.…”
Section: Invasive Grasses and Herbivore Richness On Native Hostscontrasting
confidence: 92%
See 1 more Smart Citation
“…According to this second hypothesis, we also would expect a unimodal variation in herbivore richness along the gradient of invasion by nonnative grasses through the effect of past disturbances on host plants. Why did we find a peak in insect richness at intermediate invasion levels, whereas several previous studies have reported a monotonic decline in insect richness in habitats invaded by nonindigenous plants (e.g., Litt and Steidl 2010;Yoshioka et al 2010)? A simple explanation is that endophagous herbivores are less susceptible to changes in vegetation structure (see Pearson 2009) and to harsher abiotic conditions (e.g., higher temperature and/or lower humidity promoting desiccation) compared to ectophagous herbivores, predators and other non-herbivorous insects.…”
Section: Invasive Grasses and Herbivore Richness On Native Hostscontrasting
confidence: 92%
“…Although some studies have shown that non-herbivorous insects are more susceptible to disturbances and changes in vegetation structure than herbivores (e.g., Pearson 2009;Litt and Steidl 2010), whether such responses also hold for non-herbivorous insects concealed within plant tissue, such as the parasitoids of endophages, remains to be determined. …”
Section: Invasive Grasses and Herbivore Richness On Native Hostsmentioning
confidence: 99%
“…Although some species respond to changes in vegetation at broader scales, animals that function at smaller scales, such as small mammals and arthropods, are more likely to respond to changes in vegetation that alter local environmental characteristics (Wiens and Milne 1989). Consequently, some taxa, including birds, mammals, and reptiles, are more likely to respond to the structural changes in the plant community that accompany WPE, whereas other taxa, especially arthropods, are also likely to respond to changes in species composition that interfere with coevolved relationships with specific plant species (Litt and Steidl 2010). Relative to vertebrates, many arthropods are less mobile, depend on a narrower range of plants for food, cover, and sites for reproduction, and can have specialized relationships with specific plant species (Kremen et al 1993).…”
Section: Animalsmentioning
confidence: 99%
“…Fourth, we examine the impact of invasive canopy cover on arthropod communities as suggested by Pawson et al (2010). The few studies that have explicitly looked into the effect of invader dominance on arthropod abundance and richness report mixed results (Heleno et al 2009;Litt & Steidl 2010;Parr, Ryan & Setterfield 2010;Pawson et al 2010;Spyreas et al 2010;Almeida-Neto, Prado & Lewinsohn 2011). Meta-analyses of a larger set of observational studies could potentially derive a more generalized view.…”
Section: Introductionmentioning
confidence: 99%